Analysis of Consumer Complaint Handling on Indonesian Consumer Site Using K-Means Cluster Method - Risma Petrus; Erma Suryani; Makarius Bajari (UPT Penerbitan Universitas Jember, 2021)
A consumer complaint is a consumer's right to submit a complaint about a service or product provided, or in other words, a complaint is an expression of consumer dissatisfaction either verbally or in writing caused by the loss experienced by the consumer and the non-fulfillment of the agreed agreement. The government is very aware of the various things experienced by consumers as users of goods and services. Through the presidential regulation of the Republic of Indonesia number 50 of 2017 concerning consumer protection strategies and through this regulation the relevant sectors make various efforts to improve their performance related to following up on every complaint. Non-hierarchical grouping using the k-means method is the placement of objects based on the closest group means. Through the results of data processing conducted through research on consumer submission data based on the type of complaint, it shows that there is significance in all variables of incoming complaints, completed complaints, complaints in process with a significance level (sig) less than 0.05. Therefore, there is a significant difference in the clusters formed that relate to all these variables. And in the table the largest F value is 355,957 which indicates that the complaints entered in each cluster are different. So it can be concluded that the greater the value of F, the greater the difference in cluster 1, cluster 2, cluster 3 for the variable concerned. Keywords: Method, K-Means, Complaint Handling, Cluster Analysis